MELT LOSS AND THE PRESERVATION OF GRANULITE FACIES MINERAL ASSEMBLAGES - White R.W.; Powell R. (My University, 2002)
The loss of a metamorphic fluid via the partitioning of H2 O into silicate melt at higher metamorphic grade implies that, in the absence of open system behaviour of melt, the amount of H2 O contained within rocks remains constant at temperatures above the solidus. Thus, granulite facies rocks, composed of predominantly anhydrous minerals and a hydrous silicate melt should undergo considerable retrogression to hydrous upper amphibolite facies assemblages on cooling as the melt crystallizes and releases its H2 O. The common occurrence of weakly retrogressed granulite facies assemblages is consistent with substantial melt loss from the majority of granulite facies rocks. Phase diagram modelling of the effects of melt loss in hypothetical aluminous and subaluminous metapelitic compositions shows that the amount of melt that has to be removed from a rock to preserve a granulite facies assemblage varies markedly with rock composition, the number of partial melt loss events and the P-T conditions at which melt loss occurs. In an aluminous metapelite, the removal of nearly all of the melt at temperatures above the breakdown of biotite is required for the preservation of the peak mineral assemblage. In contrast, the proportion of melt loss required to preserve peak assemblages in a subaluminous metapelite is close to half that required for the aluminous metapelite. Thus, if a given proportion of melt is removed from a sequence of metapelitic granulites of varying composition, the degree of preservation of the peak metamorphic assemblage may vary widely.
Keywords: GRANULITES; MELT LOSS; MELTING; METAPELITE